Extracted Pomace Olive Oil Use for the Preparation of Starch Graft Copolymer - Ola Dayoub; Sami Karam; Saeed Alkjk; Soulayman Soulayman (International Journal of Renewable Energy Development, 2022)
In this work, the relevant parameters of a pomace olive oil consecutive solvent extraction method using ethanol, and petroleum ether are investigated from dry and wet pomace samples. It is found that, oil extraction from dry samples with petroleum ether showed a high yield (11.72±0.30%) with solvent recovery of 89%, while extraction yield with ethanol is (11.1±0.60%) with solvent recovery of 90%. Moreover, it is found that the oil extraction from wet samples with ethanol is possible but the economic feasibility is not proven as the solvent recovery is of 62%. On the other hand, the possibility of hydrolysis of the crude extracted pomace oil in alkaline medium is demonstrated in this work. In this context, the starch grafting of the obtained long chain mono-fatty acids was accomplished in the presence of Fenton's reagent in a Dimethyl formamide (DMFA)/Water solution. Sonication is used for reaction mixture homogeny and the biopolymer was obtained using domestic microwave heating. After characterizing the obtained grafting polymer, it was employed to prepare a composite material with polyvinyl alcohol. The prepared PVA composite film of grafted starch (PVA/gSt) has tensile strength of (5.84 MPa) while its elongation modulus increased by 123.6%. Moreover, it was observed, in this work, that (PVA/gSt) copolymerization increases both the crystalline structure and the morphological order. This result is contrary to the available literature related to copolymerization of starch with different mono acids. It is found that, the consecutive solvent extraction method is of promising aspect from technical and economic point of view and the grafted starch compatibility with other polymers may be improved. The PVA/gSt films could be applied as packaging films.